Prevalence, clinical, and hematological profile of sickle cell disease in South Rajasthan - Mandot, Sanjay; Ameta, Gaurav (Indian Journal of Child Health, 2016)
Objectives: To know the prevalence of sickle cell disease in 0-15 years old children of tribal area and to study its clinical and hematological profile. Materials and Methods: This cross sectional study was conducted between May 2014 and December 2015 in children below 15 years of age from tribal area of Sirohi and Udaipur district in South Rajasthan. Results: A total of 1090 children in tribal area were screened for sickle cell disease. Prevalence of sickle cell disease was found to be 8.53% of which 0.77% children were suffering from sickle cell anemia (HbSS), whereas 7.7% were having sickle cell traits (HbAS). Common morbidities were anemia, pain, infection, and splenomegaly. Conclusion: Sickle cell disease is prevalent in this area. Screening for sickling in this area is suggested for early diagnosis and to promote preventive measures so as to decrease morbidity and mortality.